PENGARUH REVITALISASI DAN PENGGUNAAN SYSTEM TAPPING GATE TERHADAP PERAWATAN TOILET UMUM BERBAYAR DI PASAR INDUK KRAMAT JATI - Ai Nety Sumidartini; Sukarni Novitasari (VALUTA, 2021)
Perumda Pasar Jaya again held an auction for the revitalization of the maintenance and management of the Kramat Jati main market toilet, which is in Jakarta, and currently the winner of the Auction from the Revitalization of Maintenance and Management is PT. Answara Sukses Perdana Indonesia, because in this case in order to create a clean and comfortable market toilet. So that market visitors are more comfortable to enter the traditional market. The management and maintenance of toilets on the market today is constantly improving every year. This is in accordance with the slogan of Pasar Jaya which wants to create a clean and healthy market scope. Market management wants toilet cleanliness to be one of the benchmarks in seeing market feasibility. "Because even though it's a traditional market, cleanliness can't be taken for granted, we want the impression of dirty and dirty market toilets to change in the community, considering that we continue to pursue repairs and maintenance of toilets to make them better," he said. improvement of market toilets to participate in these activities. It is hoped that in the future in a number of markets, the toilets can be even better. Previously, one of the standard toilet revitalization and maintenance programs using the Tapping Gate System could be seen at the Kramat Jati Main Market, East Jakarta, where improvements were made for the users of the public toilet services. The most prominent improvements made by the management are revitalization and maintenance and the implementation of a tapping gate system in market toilets whose standards are equivalent to toilets in five-star hotels. Because it is used as one of the standards in the future, every market belonging to PD Pasar Jaya which is revitalized in its model and shape and must use the Tapping Gate system and must refer to the toilets in the market. Because it is built to a standard, the maintenance is also not the same as the others/markets that have not been revitalized and have not used the Tapping gate system. Its management is also expected to be a reference for other markets. Management and maintenance of this market toilet, especially in terms of cleanliness, supporting facilities and size. That's why you need to be careful when doing it. So that it can provide convenience to traders and people who come to shop at traditional markets